Aspirin usage is associated with improved prosthetic infrainguinal bypass graft patency. (April 2014) - Gassman, AA; Degner, BC; Al-Nouri, O; Philippi, L; Hershberger, R; Halandras, P; Aulivola, B; Milner, R
The American Heart Association recommends that, unless contraindicated, all patients undergoing surgical revascularization for critical limb ischemia should be placed postoperatively on antiplatelet therapy and remain on it indefinitely. The goal of this study was to evaluate if preoperative use of aspirin was associated with improved bypass grafting patency rates and limb salvage. We performed a four-year, retrospective review of one center's experience with open infra-inguinal bypass. We examined the effect pre- and postoperative usage of antiatherosclerotic agents (i.e. aspirin, statin, etc.) have on graft outcomes such as two-year secondary patency, stenosis and limb salvage via univariate Kaplan–Meir survival curve analysis and multiple regression analysis. Our cohort included 165 bypasses in individuals with multiple co-morbidities. The most frequent indication was critical limb ischemia (79%) and most bypasses crossed the knee (63%). Pre- and postoperative aspirin usage was associated with increased two-year secondary prosthetic graft patency over control (preoperative: 78% versus 44%, P < 0.002 and postoperative: 72% versus 50%, P < 0.01). Preoperative aspirin usage was associated with an improvement in the rate of amputation (odds ratio [OR] = 0.44 [95% CI 0.198–0.997]) and stenosis (OR = 0.45 [95% CI 0.217–0.956]). Medications commonly prescribed for atherosclerosis such as aspirin are associated with a significant patency benefit when administered pre- and postoperatively. In a population undergoing infrainguinal bypass with prosthetic graft for predominantly critical limb ischemia, medical optimization should include both pre- and postoperative antiatherosclerotic drug regimens.